Substance Use Disorder Treatment in the Reentry Environment: Service Receipt and Prisoner Community Reintegration. (September 2019) - Hamilton, Leah; Belenko, Steven
Accessing substance use disorder (SUD) treatment after prison is a challenging process for released inmates. Pre-release behavioral health services appear to improve treatment access. However, a deeper understanding of pre-release services in facilitating treatment after release, as well as how pre-release services are affected by the introduction of post-release services, are needed to determine how to best facilitate SUD treatment access with this population. Using the Serious and Violent Offenders Reentry Initiative male dataset ( N = 1, 697), the relationship between pre-release behavioral health services and SUD treatment at 3 and 9 months after release is examined. The results demonstrated that only a few pre-release services, along with individual motivation, maintained their influence on SUD treatment access over both follow-up time points; however, other services provided later into the post-release re-entry process also contributed to improved SUD treatment receipt. Implications for improving transition services for inmates with SUDs are discussed